Evaluation of phytochemicals, antioxidant contents and in vitro antioxidant activities of a combined ethanol extract of Spermacoce radiata and Hypselodelphys poggeana leaves - Robert Ikechukwu Uroko; Chinedu Aguwamba; Chinomso Friday Aaron; Paul Nweje-Anyalowu; Mercylyn Ezinne Uche (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: Oxidative stress causes lipid peroxidation, damages various macromolecules, tissues and organs, and is involved in the pathogenesis of several diseases. Antioxidant supplementation could help scavenge free radicals and prevent oxidative stress. This study evaluated the phytochemicals, antioxidant compositions and in vitro antioxidant activities of a combined extract of Spermacoce radiata and Hypselodelphy spoggeana leaves (CEESH). Experimental: This study determined phytochemicals and antioxidant vitamins contained in CEESH. The in vitro antioxidant activities of CEESH comprising DPPH (1,1-diphenyl-2-picrylhydrazyl), nitric oxide, ferric reducing antioxidant power (FRAP), total antioxidant capacity (TAC) and thiobarbituric acid reactive substances (TBARS) were assayed. Results: The phytochemical results indicated substantial amounts of total phenols, alkaloids, and terpenoids, along with moderate amounts of tannins, flavonoids, and steroids in CEESH with a low glycoside concentration, but saponin was not detected. The plant extract also showed substantial concentrations of vitamins A, C, and E.The DPPH, nitric oxide, FRAP, TAC and TBARS for the CEESH indicated that the extract has substantial free radical scavenging activities. The CEESH demonstrated a dose-dependent significant increase in the nitric oxide, TAC, and TBARS scavenging activities, while the CEESH showed dose-dependent marked increase in FRAP within a concentration range of 40-640 µg/mL. The half-optimal effective concentration (EC50) values of the CEESH for DPPH, nitric oxide, and TBARS were 7.23, 39.40, and 63.41 µg/mL, respectively. Recommended applications/industries: These findings suggest that CEESH contains abundant phytochemicals and antioxidant vitamins and possesses high free radical scavenging potential. Therefore, CEESH could be a viable therapeutic agent for managing oxidative stress.